Marker-assisted transfer of leaf and stripe rust resistance from Triticum turgidum var. durum cv. Trinakria to wheat variety HD2932 - Mallick, Niharika; Jha, Shailendra K.; Agarwal, Priyanka; Kumar, Sachin; Mall, Anchal; M, Niranjana; Choudhary, Manish K.; Chandra, Ajay Kumar; Bansal, Shreshtha; Saharan, M. S.; Sharma, J. B.; Vinod (Frontiers in Genetics, 2022)
A marker assisted backcrossing programme initiated to transfer leaf rust resistance gene LrTrk from T. turgidum cv. Trinakria to hexaploid wheat variety HD2932 co-transferred a stripe rust resistance gene, YrTrk along with LrTrk. The cross of hexaploid recurrent parent HD2932 with tetraploid donor parent Trinakria produced pentaploid F1 plants. F1s were backcrossed with recurrent parent HD2932 to produce BC1F1 generation. Foreground and background selection was conducted in each backcross generation to identify plants for backcrossing or selfing. While foreground selection for LrTrk was carried out with linked and validated molecular marker Xgwm234, for background selection 86 polymorphic SSR markers from A and B genome were used. Single selected plant from BC1F1andBC2F1generation was backcrossed and selfed to produce BC2F1and BC2F2 generations respectively. Background selection resulted in 83.72%, 91.86% and 98.25% of RPG recovery in BC1F1, BC2F1 and BC2F2 generations, respectively. A total of 27plants with LrTrk in homozygous state were identified in BC2F2 generation and selfed to produce 27 BC2F3 NILs. All the NILs were tested for leaf and stripe rust resistance at seedling stages using 7 leaf rust and one stripe rust pathotypes. All the 27 NILs were found to be resistant to both leaf rust and stripe rust pathotypes. So, these NILs are designated to carry leaf and stripe rust resistance genes LrTrk/YrTrk.